Higher CO2 concentrations increase extreme event risk in a 1.5C world - Baker, HS; Millar, RJ; Allen, MR; Karoly, DJ; Beyerle, U; Guillod, BP; Mitchell, D; Shiogama, H; Sparrow, SN; Woollings, T; Allen, MR (Nature Publishing Group, 2018)
The Paris Agreement1 aims to ‘pursue efforts to limit the temperature increase to 1.5°C above pre-industrial levels.’ However, it has been suggested that temperature targets alone are unable to limit the risks associated with anthropogenic emissions2, 3. Here, using an ensemble of model simulations, we show that atmospheric CO2 increase - a more predictable consequence of emissions compared to global temperature increase - has a significant impact on Northern Hemisphere summer temperature, heat stress, and tropical precipitation extremes. Hence in an iterative climate mitigation regime aiming solely for a specific temperature goal, an unexpectedly low climate response may have corresponding ‘dangerous’ changes in extreme events. The direct impact of higher CO2 concentrations on climate extremes therefore substantially reduces the upper bound of the carbon budget, and highlights the need to explicitly limit atmospheric CO2 concentration when formulating allowable emissions. Thus, complementing global mean temperature goals with explicit limits on atmospheric CO2 concentrations in future climate policy would reduce the adverse effects of high-impact weather extremes.